2020
DOI: 10.1038/s41598-020-62537-3
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance in Insulator-Metal-Transition Systems

Abstract: Stochastic resonance (SR) is an ingenious phenomenon observed in nature and in biological systems but has seen very few practical applications in engineering. it has been observed and analyzed in widely different natural phenomenon including in bio-organisms (e.g. Mechanoreceptor of crayfish) and in environmental sciences (e.g. the periodic occurrence of ice ages). the main idea behind SR seems quite unorthodox-it proposes that noise, that is intrinsically present in a system or is extrinsically added, can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Now let us fit this unknown factor numerically. To this end, numerical simulations of the random network (1) permits to compute the time-dependent network mean V(t n ) with discrete time t n = n t and time step t and its temporal derivative 2 with respect to b yields an optimum SGS-factor b. The corresponding parameter search is done by a Particle Swarm Optimization (PSO) [68,69].…”
Section: Subgrid-scale Modeling (Sgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Now let us fit this unknown factor numerically. To this end, numerical simulations of the random network (1) permits to compute the time-dependent network mean V(t n ) with discrete time t n = n t and time step t and its temporal derivative 2 with respect to b yields an optimum SGS-factor b. The corresponding parameter search is done by a Particle Swarm Optimization (PSO) [68,69].…”
Section: Subgrid-scale Modeling (Sgs)mentioning
confidence: 99%
“…However, noise may also be beneficial to the systems dynamics and thus represents an inevitable ingredient. In engineering, for instance, cochlear implants can improve their signal transmission rate by adding noise and thus save electrical power [2].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, SR shows a maximal output performance peak corresponding to the signal-to-noise ratio at a moderate optimal noise level. Since Benzi et al first suggested this phenomenon and its underlying mechanism in a study on ice-age cycles [2,3], SR has been extensively investigated in various fields, including physics [4,5], chemistry [6,7], biology [8,9], information technology [10,11], and brain science [12,13]. In contrast, an opposing phenomenon known as the inverse stochastic resonance (ISR) was initially discovered in a neural system [14][15][16], showing a minimal output performance peak at a moderate optimal noise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the commonly used amplitude noise, our method consisted in using the, usually overlooked, phase noise [25,26]. Moreover, we used a colored noise with a finite autocorrelation time (c ≠ 0) [17,21,22,[27][28][29][30][31], instead of the conventional quasi-white noise (c ≈ 0) [2][3][4][5][6][7][8][9][10][11][12][13]27].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was discovered in the nervous systems of crayfish and paddlefish as an evolutionary mechanism, resulting in its importance in neurobiological research [35], [36]. Recently, several engineering applications which use this phenomenon have also emerged, such as a visual aid [37], a low power photodetector [38], an Insulator-Metal Transition (IMT) system [39]. Few papers [40], [41] have presented device applications for weak electronic signal detection.…”
Section: Introductionmentioning
confidence: 99%